2022
DOI: 10.1039/d1nj05120b
|View full text |Cite
|
Sign up to set email alerts
|

Construction of highly dispersed Au active sites by ice photochemical polishing for efficient acetylene hydrochlorination

Abstract: Considering the economic and environmental advantages of water as a solvent and the drawbacks of Au catalyst prepared in an aqueous solution for acetylene hydrochlorination, such as easy aggregation of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In the case of 15% Cu 8 MDPO 1 /AC, a sharp decrease in the mass was observed at 260 and 220 °C for the fresh and spent catalysts, respectively. Considering that decomposition of MDPO did not occur at the reaction temperature (Figure S3b), the weight loss difference between the unreacted catalyst and the reacted catalyst at the intermediate stage can be attributed to the amount of coking deposition on the catalyst during the reaction process . It was found that the most serious carbon deposition (3.99%) occurred on the surface of the benchmark catalyst 15% Cu/AC (Figure S3c), which would ultimately annihilate the active sites and block the mass transfer channels of reactants and product molecules, causing a rapid decrease in the catalyst activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of 15% Cu 8 MDPO 1 /AC, a sharp decrease in the mass was observed at 260 and 220 °C for the fresh and spent catalysts, respectively. Considering that decomposition of MDPO did not occur at the reaction temperature (Figure S3b), the weight loss difference between the unreacted catalyst and the reacted catalyst at the intermediate stage can be attributed to the amount of coking deposition on the catalyst during the reaction process . It was found that the most serious carbon deposition (3.99%) occurred on the surface of the benchmark catalyst 15% Cu/AC (Figure S3c), which would ultimately annihilate the active sites and block the mass transfer channels of reactants and product molecules, causing a rapid decrease in the catalyst activity.…”
Section: Resultsmentioning
confidence: 99%
“…Further, the introduction of the Cu precursor resulted in a strong desorption at 337 °C for Cu/AC, which is mainly related to the adsorption and activation of HCl by the electron cloud around the Cu active center. Notably, the introduction of the MDPO ligand having a highly reactive benzene ring-containing PO structure that can form hydrogen bonds with HCl triggered the multistate adsorption of the 15% Cu 8 MDPO 1 /AC catalyst with an enhanced adsorption capacity . This may be related to the increased density of the electron cloud around the active centers, which results from the coordination of the Cu precursor with the ligand, promoting the transfer of electrons from the heteroatom to the Cu n+ species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few decades, gold-based catalysts have been some of the most promising catalysts among the many transition metal catalysts, such as Au-based, [7][8][9][10][11][12] Pd-based, [13][14][15] Ru-based, [16][17][18][19][20] Bi-based 21 and Cu-based [22][23][24][25][26] catalysts, owing to their excellent catalytic activity and stability, but the high cost and low reserve prohibit the large-scale utilization of Au-based catalysts for acetylene hydrochlorination. Recently, carbonaceous materials have generally been employed in various reactions, such as the CO 2 reduction reaction, 27 the oxygen reduction reaction, 28 cellulose hydrolysis, 29 hydrazine oxidation, 30 and so on.…”
Section: Introductionmentioning
confidence: 99%